Influence of Operational Agility on Employees' Performance in Pharmaceutical Industries in Kwara State - Moriam Adeyemi Aremu; Risikat Bola Sulaiman; Taiye Hassan Ahmed (Ecobankers : Journal of Economy and Banking, 2025)
Poor operational agility has been recognised as a factor affecting employees' performance. Adequate technological infrastructures, innovative capabilities, and digital transformation systems are reported to enhance workers' performance. This study examined the influence of operational agility on employees’ performance. A descriptive survey was used. The population was 435 staff of Tuyil Pharmaceutical, Ilorin. The sample was 208 employees, calculated using Taro Yamane's formula for sample size determination. A structured "Operational Agility and Employee Performance Questionnaire (OAEPQ)” was used for data collection. The reliability of the adopted questionnaire was assessed at Cronbach’s Alpha (α) with a reliability score of 0.86. Data analysis was conducted using frequency and percentage to present the answer to the research question. Regression Analysis was used to test the research Hypothesis at a 0.05 significance level. Findings showed that adaptation to technological infrastructures. Innovative capabilities and deployment of product delivery systems exert little influence on employee performance. Adopting modern IT applications for dynamic business operation processes increased employee activity efficiency. Digital transformation of systems improved employees’ efficiency, showing a greater influence on employees’ performance. Based on the findings, the study concluded that digital transformation and adopting modern IT applications for dynamic business operation processes strongly influence employees’ performance. The study recommends that employers ensure more adaptation to technological infrastructures, enhance the innovative capabilities of employees and implement massive deployment of product delivery systems to customers.